LEARNING INNOVATION: IMPLEMENTATION OF THE INQUIRING MINDS WANT TO KNOW LEARNING MODEL IN GRADE V PRIMARY SCHOOL OF MUHAMMADIYAH BIAK - Hasanah, Siti Nur; Efendi, Didik (Waniambey: Journal of Islamic Education, 2024)
One way to increase student motivation to learn is to use a learning model in accordance with the student's character. Researchers chose the Inquiring Mind Want to Know model from the various strategies available to be applied to science learning in Grade V Primary School of Muhammadiyah Biak. This study aimed to determine the Learning Innovation: Implementation of Inquiring Mind Want to Know Model in Grade V Primary School of Muhammadiyah Biak. This study conducted descriptive qualitative research with a case study. The three methods of data collection are observation, interview, and documentation. However, the data analysis method includes collection, reduction, presentation, and conclusion.Furthermore, triangulation was used to ensure the validity of the data. The results showed several ways to implement the Inquiry Mind Want to Know model in science learning. One of them is by directly practising the steps of the model. The disadvantage is that students do not have enough time to learn, but the advantage factor is that students have enough time to learn actively. One of the impacts of the Inquiry Mind Want to Know model on science learning is that students are more actively involved in the learning process with their curiosity, students can expand their knowledge of attitudes and skills, especially in science, and teachers more easily understand their students